Pendampingan Pembentukan Flower Bank sebagai Upaya Peningkatan Perekonomian Masyarakat di Desa Gentengwetan Kecamatan Genteng Kabupaten Banyuwangi - Susanti, Nawal Ika; Hikmah, Siti Nur Afifatul; Insaniyah, Anyes Lathifatul (Proceedings of Annual Conference on Community Engagement, 2022)
The establishment of this flower bank was also carried out as one of the community’s efforts to be able to improve the household economy after the Covid-19 pandemic. The target is housewives in Dusun Krajan together with Youth Organization. This assistance is needed as a follow-up to the Village Government Program, namely the movement to plant flowers. The interest generated from this movement to plant interest can be sold in Flower banks and the money from the sale of interest is collected in the form of savings. The method used in this assistance uses a Participatory Action Research. Assistance steps include outreach to the public about Flower banks, training and administrative practices for Flower banks. The impact of this assistance is the enthusiasm of the community towards the Flower Bank in Dusun Krajan, changes in the family’s economy and the establishment of partnerships with flower shops around Dusun Krajan.